2017
DOI: 10.1371/journal.pone.0186056
|View full text |Cite
|
Sign up to set email alerts
|

Generation of beta-lactoglobulin knock-out goats using CRISPR/Cas9

Abstract: Goat’s milk, considered a substitute for cow’s milk, has a high nutritional value. However, goat’s milk contains various allergens, predominantly β-lactoglobulin (BLG). In this study, we employed the CRISPR/Cas9 system to target the BLG locus in goat fibroblasts for sgRNA optimization and generate BLG knock-out goats through co-injection of Cas9 mRNA and small guide RNAs (sgRNAs) into goat embryos at the one-cell stage. We firstly tested sgRNA editing efficiencies in goat fibroblast cells, and approximately 8.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 43 publications
(56 reference statements)
0
37
0
Order By: Relevance
“…Therefore, the creation of a sCAT line with higher Cas9 expression is desirable. Our most important finding, however, is that this novel gene-editing system based on the use of maCas9 considerably facilitates the generation of mice with single and multiple gene modifications and could be applied to various animal species other than mice [16][17][18][19][20] . In addition, similar effects could be obtained using other Cas proteins 41,42 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the creation of a sCAT line with higher Cas9 expression is desirable. Our most important finding, however, is that this novel gene-editing system based on the use of maCas9 considerably facilitates the generation of mice with single and multiple gene modifications and could be applied to various animal species other than mice [16][17][18][19][20] . In addition, similar effects could be obtained using other Cas proteins 41,42 .…”
Section: Discussionmentioning
confidence: 99%
“…The two main genotypes of PRRS virus (PRRSV) share about 60% sequence identity, with further genetic disparity between isolates within each genotype. Control is generally with modified live vaccines, but cross-protection between viral strains is poor [28] . In vitro studies identified CD163, a member of the scavenger receptor cysteine-rich superfamily, as necessary for establishment of a productive viral infection [29] .…”
Section: Disease Resistancementioning
confidence: 99%
“…Targeted genome modifications have modernized the field of genome engineering and biotechnology by GenEd from unicellular to multicellular and from prokaryotic to eukaryotic organisms. A diversity of organisms from bacteria to humans such as Arabidopsis thaliana [1], tobacco [2], rice [3], yeast (Saccharomyces cerevisiae) [4], fungi [5], zebrafish [6], rats [7], sheep [8], Caenorhabditis elegans [9], human cell lines [10], Drosophila [11], viruses [12][13][14], bacteria [15], mouse [16], insects [17], cattle [18], goat [19], pigs [20], tomato [21], grapes [22], potato [23], soybean [24], maize [25], wheat [26], and cotton [27,28] have been targeted successfully with engineered proteins and nucleases.…”
Section: Gened Tools For Targeted Genome Modificationmentioning
confidence: 99%
“…Multiplexing through CRISPR/Cas9 has been used successfully in model and crop plants [19,66,67]. Multiplex genome editing may also be useful for studying functions of gene families as well as an interaction between multiple genes.…”
Section: Use Of Gened Tools Against Abiotic Stresses In Cottonmentioning
confidence: 99%